Analysis and Validation of Ultrasonic Probes in Liquid Level Monitoring Systems - Wanjia Gao; Wenyi Liu; Fei Li; Yanjun Hu (Sensors, 2021)
Selecting and designing the optimum ultrasonic probe is vital for ultrasonic measurements and experiments. The amplitude of the emitted ultrasonic wave excitation signal as well as the diameter and the natural frequency of the probe seriously affect the validity of the probe results. In this paper, we analyze the significance of the key parameters of the ultrasonic probe theoretically. Further, an external fixed-point liquid level monitoring system was assembled according to the principle of ultrasonic reflection and transmission. On this experimental platform, we study the key parameters of the ultrasonic probe that affect the system evaluation through a simulation and experiment, and select the optimal sensor parameters for this experiment. The evaluations show that under the experimental conditions where the tested container is made of aluminum alloy and its wall thickness is 3 mm, the best results are obtained when the diameter of the ultrasonic sensor is 15 mm, the amplitude of the emitted excitation signal is ±15 V, and the frequency is 1 MHz. The results’ average deviation is less than ±0.22 V. The evaluations are consistent with the simulation results. This research can effectively monitor the liquid in the closed, ultra-thin-walled container, and can realize non-contact measurement. It provides an effective basis for the parameters selection and design of the ultrasonic probe in the ultrasonic-based experiments and tests.